Ectonucleotidases in Acute and Chronic Inflammation - Giuliani, Anna Lisa; Sarti, Alba Clara; Di Virgilio, Francesco (Frontiers in Pharmacology, 2021)
Ectonucleotidases are extracellular enzymes with a pivotal role in inflammation that hydrolyse extracellular purine and pyrimidine nucleotides, e.g. ATP, UTP, ADP, UDP, AMP and NAD+. Ectonucleotidases, expressed by virtually all cell types, immune cells included, either as plasma membrane-associated or secreted enzymes, are classified into four main families: 1) nucleoside triphosphate diphosphohydrolases (NTPDases), 2) nicotinamide adenine dinucleotide glycohydrolase (NAD glycohydrolase/ADP-ribosyl cyclase/cyclic ADP-ribose hydrolase 1), 3) ecto-5′-nucleotidase (NT5E), and 4) ecto-nucleotide pyrophosphatase/phosphodiesterases (NPPs). Concentration of ATP, UTP and NAD+ can be increased in the extracellular space thanks to un-regulated, e.g. cell damage or cell death, or regulated processes. Regulated processes include secretory exocytosis, connexin or pannexin hemichannels, ATP binding cassette (ABC) transporters, calcium homeostasis modulator (CALMH) channels, the ATP-gated P2X7 receptor, maxi-anion channels (MACs) and volume regulated ion channels (VRACs). Hydrolysis of extracellular purine nucleotides generates adenosine, an important immunosuppressant. Extracellular nucleotides and nucleosides initiate or dampen inflammation via P2 and P1 receptors, respectively. All these agents, depending on their level of expression or activation and on the agonist concentration, are potent modulators of inflammation and key promoters of host defences, immune cells activation, pathogen clearance, tissue repair and regeneration. Thus, their knowledge is of great importance for a full understanding of the pathophysiology of acute and chronic inflammatory diseases. A selection of these pathologies will be briefly discussed here.